Knowledge: its role in hunger, nutrition and climate justice - Vermeulen, Sonja J.; Moussa, Abdoulaye S.; Bonilla Findji, Osana; Bhatta, Gopal Datt; Radeny, Maren A.O. (2013)
Climate change will change conditions for food and farming beyond all previous human experience. We need a new era of innovation, in which farmers and communities participate in learning networks, drawing on science and on others’ experiences to complement their local knowledge.